Factors associated to smoking habit among older adults (The Bambuí Health and Aging Study) Fatores associados ao hábito de fumar entre idosos (Projeto Bambuí) - Sérgio Viana Peixoto; Josélia Oliveira Araújo Firmo; Maria Fernanda Lima-Costa (Universidade de São Paulo, 2005)
OBJECTIVE: To describe the characteristics and associated factors of the smoking habit among older adults. METHODS: A population-based study was carried out comprising 1,606 (92.2%) older adults (>60 years old) living in the Bambuí town, Southeastern Brazil in 1997. Data was obtained by means of interview and socio-demographic factors, health status, physical functioning, use of healthcare services and medication were considered. The multiple multinomial logistic regression was used to assess independent associations between smoking habits (current and former smokers) and the exploratory variables. RESULTS: The prevalence of current and past smoking was 31.4% and 40.2% among men, and 10.3% and 11.2% among women, respectively (p<0.001). Among current smokers, men consumed a larger number of cigarettes per day and started the habit earlier than women. Among men, current smoking presented independent and negative association with age (>80 years) and schooling (>8 years) and positive association with poor health perception and not being married. Among women, independent and negative associations with current smoking were observed for age (75-79 and >80 years) and schooling (4-7 and >8 years). CONCLUSIONS: Smoking was a public health concern among older adults in the studied community, particularly for men. Yet, in a low schooling population, a slightly higher level was a protective factor against smoking for both men and women. Programs for reducing smoking in the elderly population should take these findings into consideration. OBJETIVO: Descrever as características e fatores associados ao hábito de fumar em uma população idosa. MÉTODOS: Estudo de base populacional realizado com 1.606 (92,2%) idosos (>60 anos) residentes na cidade de Bambuí, Estado de Minas Gerais, em 1997. As variáveis estudadas foram: fatores sociodemográficos, condições de saúde, função física, uso de serviço de saúde e de medicamentos. Os dados foram coletados por meio de entrevista. A regressão logística multinomial foi utilizada para avaliar associações independentes entre o hábito de fumar (atual e passado) e as variáveis exploratórias. RESULTADOS: A prevalência de tabagismo atual e passado foi de 31,4% e 40,2% entre os homens, e de 10,3% e 11,2% entre as mulheres, respectivamente (p<0,001). Entre os tabagistas atuais, os homens consumiam maior número de cigarros diários e iniciaram o hábito mais cedo do que as mulheres. Entre os homens, o tabagismo atual apresentou associação independente e negativa com idade (>80 anos) e escolaridade (>8 anos) e associação positiva com percepção ruim da saúde e não ser casado. Entre as mulheres, associações independentes e negativas com tabagismo atual foram observadas para idade (75-79 e >80 anos) e escolaridade (4-7 e >8 anos). CONCLUSÕES: O tabagismo constituiu um problema de saúde pública entre os idosos da comunidade estudada, sobretudo no sexo masculino. Mesmo em uma população de baixa escolaridade, o grau de instrução foi fator protetor para o tabagismo em ambos os sexos. Programas para a redução do tabagismo na população idosa deveriam levar estes resultados em consideração.